Alqurun Teaching Model-Based Trigonometry Teaching Material - Putra, Rizki Wahyu Yunian; Suherman, Suherman; Anggoro, Bambang Sri; Pamungkas, Aan Subhan (Universitas Islam Negeri Raden Intan Lampung, 2020)
Learning in the industrial era 4.0 requires innovation in the development of teaching materials. The purpose of this research is to develop a valid and attractive Alqurun Teaching Model (ATM) teaching material for learning trigonometry. This research was a development research using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data were collected using a questionnaire. The small group test was conducted by 9 respondents and the large group test was carried out by 12 respondents. The results showed that based on material experts, this teaching material received a feasibility score of 4.06, 4.78 from media experts, and 4.19 from linguists, all of which indicated that this teaching material was in the very feasible category. The results of the small and large group tests showed a score of 3.36 and 4.21, meaning that this teaching material was very interesting. So, it can be concluded that this teaching material can be used in learning trigonometry.